INFORMATION SECURITY BEHAVIOR AMONG MALAYSIAN SMES: PHISHING, CYBERSECURITY INCIDENT, HUMAN FACTORS AND RISK MITIGATION - Mohamad Arifin, Mohamad Syauqi; Mohamad Rosman, Mohamad Rahimi; Md Radzi, Salliza; Mat Nawi, Nur Ainatul Mardiah; Alimin, Noor Azreen (Journal of Islamic, Social, Economics and Development, 2024)
Information security concerns is one of the most important issues faced by Malaysian Small and Medium Enterprise (SMEs). The rise of cybersecurity threat especially in digital environment caused losses to Malaysian’s SMEs and preventing nationwide digitalization efforts. Thus, more efforts, services, and campaign are needed to revive the digital platform among Malaysian’s SMEs. Three important issues faced by Malaysian’s SMEs are related to phishing, cybersecurity incidents, and human factors. Therefore, this paper study the literature on the underlying cause of information security behavior among Malaysian’s SMEs – and subsequently underlying the future research direction..